Vlasov's Physics: From Plasma to Solid - Talanin, V. I.; Talanin, I. E. (Advanced Aspects of Engineering Research Vol. 3, 2021)
The basic principles of Vlasov's physics are considered from a general point of view. The reliability of his judgments about the application of nonlocal statistical mechanics to real solids is shown. The possibilities of Vlasov's physics for a reliable description of matter are discussed.